FORMAL MATHEMATICAL COMPETENCE. APPLICATIONS FOR CONTENT ANALYSIS AND CURRICULAR DEVELOPMENT IN MATHEMATICS - Socas Robayna, Martín. M.; Ruano Barrera, Raquel (Atenas, 2014)
Different assessments in mathematics show that the students’ knowledge of mathematics is unsatisfactory. How can the teaching and learning of mathematics be improved? This paper studies mathematical culture by analysing three essential aspects which characterize it: the conceptual field, problem-solving and language. This will help to describe Formal Mathematical Competence (FMC) with regard to numerical and algebraic fields. The paper will also analyze strategies and tasks connected to mathematical content analysis and curricular development. This will aid the development of professional competences and a more effective teaching of mathematics on the part of these teachers.